Extreme Loads on Jacket Structures : Effect of Higher Order Linearities and Momentum Flux Formulation - Ng , Weng Jie (Universiti Teknologi PETRONAS, 2020)
Jacket structures make up majority of oil platforms in Malaysia. Although reassessments have always been conducted from time to time, existing structures may now be subjected to more critical conditions due to several reasons which include the desire to extend the life of the existing structure. Concerns are raised even more since the existing structures in Malaysia have only been designed to resist regular wave loadings and have neglected other load cases. Therefore, this study aims to assess the structure under irregular wave loadings, compare the loadings on the structure when effects of currents are considered and to compute the magnitude of wave-in-deck on the jacket structure. The methodology for the research has been separated into three distinct stages. The first stage is to develop the code, followed by computing wave and current loadings and the last stage is to include wave-in-deck loads.